Strategi Rekrutmen dan Seleksi pada Proyek Penunjukan langsung di PT. XYZ. - Himalaya Bima Kenzo; Ghina Rizqandi Q.A; Dwi Aneka Kartini (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2025)
Human resources play a very important role, according to a report from the World Economic Forum (2020), around 60% of the total construction project costs are allocated to labor costs. Apart from that, the construction industry also has to compete with other sectors that offer more attractive salaries and working conditions. A study by McKinsey & Company (2017). Selection is the process of evaluating candidates to determine whether they are qualified for the position offered. According to Schmidt and Hunter (1998), effective selection can improve employee performance and reduce turnover rates. Many workers are unfamiliar with new technology and find it difficult to adapt. Innovation in recruitment and selection is also the key to the company's success in facing challenges in the construction sector. By adopting new technologies and more effective selection methods, companies can improve the quality of their workforce and ensure the success of future projects. By understanding the challenges faced and implementing best practices in recruitment and selection, companies can attract and retain a quality workforce.